2021
DOI: 10.3390/jcm10040740
|View full text |Cite
|
Sign up to set email alerts
|

Neuromonitoring of the Recurrent Laryngeal Nerve Reduces the Rate of Bilateral Vocal Cord Dysfunction in Planned Bilateral Thyroid Procedures

Abstract: Purpose: Bilateral vocal cord dysfunction (bVCD) is a rare but feared complication of thyroid surgery. This long term retrospective study determined the effect of intraoperative neuromonitoring (IONM) of the recurrent laryngeal nerve (RLN) during thyroid surgeries with regard to the rate of bVCD and evaluated the frequency as well as the outcome of staged operations. Methods: Retrospective analysis of prospectively documented data (2000–2019) of a tertiary referral centers’ database. IONM started in 2000 and, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…One further patient ended up having an aggressive thyroid cancer after abortion of planned total thyroidectomy. Other authors did not report or reported limited information regarding complications among completion thyroidectomy cases . However, the number of cases undergoing completion thyroidectomy in this study is very low, so caution should be exercised drawing any conclusions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…One further patient ended up having an aggressive thyroid cancer after abortion of planned total thyroidectomy. Other authors did not report or reported limited information regarding complications among completion thyroidectomy cases . However, the number of cases undergoing completion thyroidectomy in this study is very low, so caution should be exercised drawing any conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…While IONM can offer the significant benefit of nearly eliminating the risk of bilateral VCP after thyroidectomy by prompting the surgeon to abort the operation in case of first-side LOS, [12][13][14] this approach may lead to failure to resolve symptoms, delay in treatment, and patient dissatisfaction due to need for a secondary procedure. There are also risks of morbidity from the second procedure, which may be increased due to scarring from the first operation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In another paper, the advantages of the application of intraoperative neuromonitoring of the recurrent laryngeal nerve (IONM) were shown, which, according to authors' findings, reduces the rate of one of the most important complications of thyroid surgeries in bilateral planned thyroidectomies -bilateral vocal cord dysfunction (bVCD) [21]. This retrospective analysis involved prospectively documented data from 20-year experience of a tertiary referral center.…”
mentioning
confidence: 99%